A fast-charging battery and an electric device

CN122800708APending Publication Date: 2026-09-22CALB GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611150028.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

行业主流应用的石墨负极,受自身微观结构限制,存在如下动力学缺陷:一方面,负极表层可供锂离子嵌入的有效通道数量偏少,当接入大电流进行充电时,大量锂离子涌向负极界面,有限的嵌入通道无法快速承接嵌锂反应,极易造成界面锂离子堆积;另一方面,锂离子进入负极颗粒后,需要沿固相内部完成长距离扩散迁移,较长的扩散路径进一步降低了离子传输速率

Benefits of technology

[0011]本发明提供的快充电池通过对石墨负极的二次颗粒中包含一次颗粒的平均数、一次颗粒的平均粒径以及电解液的离子电导率等关键参数的协同调整,实现了负极微观结构和电解液电导率的动态匹配,有效打通锂离子传输通道、缩短扩散路径,很好地兼顾了快充电池的动力学和高温存储性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800708A_ABST
    Figure CN122800708A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and relates to a fast-charging battery and an electric device, the fast-charging battery comprising a negative electrode sheet and an electrolyte, the negative electrode sheet comprising a negative electrode active material, the negative electrode active material containing graphite, and the fast-charging battery having a charging time of less than or equal to 15 min from 10% SOC to 80% SOC; the negative electrode active material comprising secondary particles formed by agglomeration of primary particles, the average number of primary particles contained in the secondary particles being set as N, the average particle size of the primary particles being d microns, and the ionic conductivity of the electrolyte at 25 DEG C being sigma mS / cm, and the following condition being met: 3.1 <= (N*sigma) / d <= 21.7. The fast-charging battery provided by the application optimizes the microstructure parameters of the negative electrode active material and the ionic conductivity range of the electrolyte in a synergistic manner, opens up the lithium ion transmission channel, shortens the diffusion path, and significantly improves the fast-charging performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology and relates to a fast-charging battery and an electrical device. Background Technology

[0002] Currently, the rapid development of new energy passenger vehicles, portable digital devices, and energy storage terminals has led to increasingly higher market demands for the fast-charging performance of lithium-ion batteries. Minimizing charging time and achieving rapid energy replenishment has become a crucial direction for battery technology iteration. Major research institutions and companies are conducting extensive research on fast-charging technology. However, based on the actual performance of existing commercial battery systems, overall charging efficiency still has significant shortcomings. Charging time is relatively long under normal operating conditions, and the user experience, especially in high-rate fast-charging scenarios, fails to meet user requirements.

[0003] After in-depth analysis of the battery charging and discharging reaction mechanism, researchers discovered that the migration, insertion, and extraction efficiency of lithium ions directly determines the battery's charging speed, and the anode active material is a key factor affecting the lithium ion transport process. The graphite anode, which is the mainstream material used in the industry, suffers from the following kinetic defects due to its microstructure: Firstly, the number of effective channels for lithium ion insertion on the anode surface is limited. When a large current is applied for charging, a large number of lithium ions rush to the anode interface, and the limited insertion channels cannot quickly accommodate the lithium insertion reaction, easily leading to lithium ion accumulation at the interface. Secondly, after entering the anode particles, lithium ions need to complete long-distance diffusion and migration along the solid phase, and the longer diffusion path further reduces the ion transport rate.

[0004] It is evident that the hindered interfacial lithium intercalation, coupled with slow internal diffusion, ultimately affects the electrochemical reaction kinetics on the negative electrode side, thus making the negative electrode side a bottleneck restricting the battery's fast-charging performance. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a fast-charging battery and power device that opens up the lithium-ion transport channel, shortens the diffusion path, and improves the fast-charging performance of the battery.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a fast-charging battery, comprising a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode active material, the negative electrode active material contains graphite, and the charging time of the fast-charging battery from 10% SOC to 80% SOC is ≤15 min.

[0008] The negative electrode active material includes secondary particles formed by the agglomeration of primary particles. The average number of primary particles in the secondary particles is set to N, the average particle size of the primary particles is d μm, and the ionic conductivity of the electrolyte at 25℃ is σ mS / cm. Then, the following condition is satisfied: 3.1≤(N×σ) / d≤21.7.

[0009] In a second aspect, the present invention provides an electrical device comprising a fast-charging battery as described in the first aspect.

[0010] Compared with the prior art, the present invention has the following beneficial effects:

[0011] The fast-charging battery provided by this invention achieves dynamic matching between the microstructure of the negative electrode and the conductivity of the electrolyte by synergistically adjusting key parameters such as the average number of primary particles in the secondary particles of the graphite negative electrode, the average particle size of the primary particles, and the ionic conductivity of the electrolyte. This effectively opens up lithium-ion transport channels and shortens diffusion paths, thus well balancing the dynamics and high-temperature storage performance of the fast-charging battery. Attached Figure Description

[0012] Figure 1 This is a micrograph of the negative electrode active material in the fast-charging battery provided in Example 1. Detailed Implementation

[0013] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0014] One embodiment of the present invention provides a fast-charging battery, including a negative electrode sheet and an electrolyte. The negative electrode sheet includes a negative electrode active material containing graphite. The charging time of the fast-charging battery from 10% SOC to 80% SOC is ≤15 min, for example, it can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0015] This invention specifically limits the charging capacity range of the fast-charging battery to 10% SOC to 80% SOC because within this range, the graphite anode has sufficient lithium intercalation sites, exhibits the best kinetic performance, facilitates smooth lithium-ion intercalation, ensures the safest high-current charging, and achieves the highest efficiency—the golden range for fast charging. If the charging capacity range is too low (e.g., 0% SOC to 10% SOC), the battery voltage is low, polarization is significant, lithium intercalation is weak, and high current can easily lead to lithium metal deposition, even puncturing the separator, causing bulging, and fire, making it unsuitable for high-current fast charging. If the charging capacity range is too high (e.g., 80% SOC to 100% SOC), the graphite layer is almost completely filled with lithium, leaving very few vacancies. This causes a sharp increase in lithium intercalation resistance, and continued high-current charging will result in a large amount of lithium failing to intercalate and directly depositing, leading to a dramatic thickening of the SEI film, severe heat generation, and a precipitous degradation during cycling.

[0016] Based on this, the present invention further limits the charging time of the fast-charging battery from 10% SOC to 80% SOC to ≤15min, which well balances the four major boundaries of user energy replenishment efficiency, cell heat generation control, negative electrode lithium plating safety, and cycle life, and represents the optimal fast-charging balance point of current liquid lithium batteries.

[0017] In this invention, the negative electrode active material includes secondary particles formed by the agglomeration of primary particles. The average number of primary particles in the secondary particles is set to N, and the average particle size of the primary particles is d μm. The ionic conductivity of the electrolyte at 25°C is σ mS / cm, which satisfies: 3.1 ≤ (N × σ) / d ≤ 21.7. For example, it can be 3.1, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, or 21.7, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0018] In the above parameter relationships, increasing the average number N of primary particles contained in secondary particles can reduce the degree of order in the graphite sheet arrangement direction, which is beneficial to increasing the number of lithium-ion insertion channels at the interface of the negative electrode active material, shortening the lithium-ion transport path, thereby improving kinetics and fast-charging performance. However, if the average number N of primary particles contained in secondary particles is too high, the reaction interface between the negative electrode active material and the electrolyte will increase, leading to more side reactions between the negative electrode active material and the electrolyte, affecting high-temperature storage performance. To address this, increasing the average particle size d μm of primary particles can reduce the reactive surface area between the electrolyte and the negative electrode active material, improving high-temperature cycling performance. However, if the average particle size d μm of primary particles is too large, it will lead to a longer lithium-ion transport path in the negative electrode active material, adversely affecting kinetics. Therefore, further control of the ionic conductivity σ mS / cm of the electrolyte can reduce the transport resistance of lithium ions in the electrolyte, improve lithium-ion transport performance, and thus improve kinetics.

[0019] Therefore, this invention comprehensively controls the numerical range of (N×σ) / d. If the parameter relationship exceeds 21.7, the high-temperature storage performance deteriorates; if the parameter relationship is less than 3.1, the fast-charging performance deteriorates. By limiting 3.1≤(N×σ) / d≤21.7, this invention effectively balances the dynamics of fast-charging batteries and high-temperature storage performance.

[0020] In some embodiments, the OI value of the negative electrode active material is 2 to 3.84, for example, it can be 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8 or 3.84, preferably 2.5 to 3.5, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0021] In this invention, the OI value of the negative electrode active material specifically refers to the ratio of the peak area of ​​the (004) crystal plane to the peak area of ​​the (110) crystal plane of graphite, which is used to characterize the degree of orientation order of graphite sheets. It can be calculated by testing the XRD pattern of graphite at 10-90° using an X-ray diffractometer.

[0022] This invention limits the OI value of the negative electrode active material to the range of 2 to 3.84, which corresponds to a reasonably low level of ordered graphite sheet arrangement. This can effectively increase the number of lithium-ion insertion sites at the negative electrode interface and shorten the lithium-ion solid-phase transport path, thereby improving the electrode reaction kinetics and meeting the requirements of high-current fast charging.

[0023] In some embodiments, the average number N of primary particles contained in the secondary particles is 3 to 15, for example, it can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, preferably 4 to 8, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0024] In some embodiments, the average particle size d μm of the primary particles is 3 to 9.8 μm, for example, it can be 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 9.8 μm, preferably 3.2 to 4.7 μm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0025] In some embodiments, the ionic conductivity σ mS / cm of the electrolyte at 25°C is 6.1~12.8 mS / cm, for example, it can be 6.1 mS / cm, 6.5 mS / cm, 7 mS / cm, 7.5 mS / cm, 8 mS / cm, 8.5 mS / cm, 9 mS / cm, 9.5 mS / cm, 10 mS / cm, 10.5 mS / cm, 11 mS / cm, 11.5 mS / cm, 12 mS / cm, 12.5 mS / cm or 12.8 mS / cm, preferably 8.3~9.7 mS / cm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0026] In some embodiments, the charging time of the battery from 10% SOC to 80% SOC is ≤12 min, for example, it can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min or 12 min, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0027] In some embodiments, the sphericity of the primary particles is ≥0.5, for example, it can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 0.98, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0028] In this invention, the sphericity is defined as the ratio of the surface area of ​​a sphere with the same volume as the primary particle to the actual surface area of ​​the primary particle. It is used to characterize the regularity of the shape of the primary particle. The sphericity of a perfect sphere is 1, while the sphericity of particles of other shapes is less than 1.

[0029] This invention limits the sphericity of primary particles to above 0.5, which optimizes the negative electrode particle stacking structure and ion transport channels, while also considering electrode compaction performance, lithium-ion conductivity, and interface stability. Specifically, the moderate morphology of the primary particles results in a reasonable distribution of stacked pores, ensuring smooth electrolyte wetting within the electrode and providing continuous channels for lithium-ion migration, thus adapting to high-current fast charging.

[0030] In some embodiments, the major axis of the primary particle is 6 to 12 μm, for example, it can be 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm or 12 μm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0031] In some embodiments, the minor axis of the primary particles is 2.8 to 7.4 μm, for example, it can be 2.8 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm or 7.4 μm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0032] In some embodiments, the negative electrode active material further includes individual particles discrete between primary and secondary particles.

[0033] In some embodiments, the volume percentage of the single particle in the negative electrode active material is 5% to 20%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0034] This invention limits the volume percentage of a single particle in the negative electrode active material to within the range of 5% to 20%, which can precisely control the overall particle size distribution, pore structure and ion transport network of the negative electrode active material, and optimize the overall performance of the electrode by coordinating primary and secondary particles, thereby balancing fast charging capability and interface stability.

[0035] In some embodiments, the volume percentage of the secondary particles in the negative electrode active material is 70% to 90%, for example, it can be 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88% or 90%, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0036] In some embodiments, the total volume percentage of the single particles and secondary particles in the negative electrode active material is 75% to 95%, for example, it can be 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0037] In some embodiments, the electrolyte contains a lithium salt, which includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiDFOB), lithium tetrafluoroborate (LiBF4), or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), preferably lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.

[0038] In some embodiments, the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is (0.1~0.8):(0.2~0.9), for example, it can be 0.1:0.9, 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3 or 0.8:0.2, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0039] In some embodiments, the electrolyte contains a solvent comprising at least one of cyclic carbonates, chain carbonates, carboxylic acid esters, or ethers, preferably a chain carbonate comprising at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), or diethyl carbonate (DEC).

[0040] In some embodiments, the number of carbon atoms in the chain carbonate is ≤5, for example, it may be 1, 2, 3, 4 or 5.

[0041] In some embodiments, the electrolyte contains an additive, which includes at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), or ethylene disulfide (BiDTD).

[0042] In some embodiments, the additive accounts for 0.5 wt% to 10 wt% of the electrolyte by mass, for example, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, or 10 wt%, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0043] In some embodiments, the fast-charging battery further includes a positive electrode sheet comprising a positive electrode material containing lithium iron phosphate. The charging time of the fast-charging battery from 10% SOC to 80% SOC is ≤12 min, for example, it can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min or 12 min. The corresponding fast-charging battery satisfies: 3.2≤(N×σ) / d≤17.8, for example, it can be 3.2, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 17.8, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0044] In some embodiments, the fast-charging battery further includes a positive electrode sheet comprising a positive electrode material containing a ternary material. The nickel content in the ternary material is 60 wt% to 88 wt%, for example, it can be 60 wt%, 62 wt%, 64 wt%, 66 wt%, 68 wt%, 70 wt%, 72 wt%, 74 wt%, 76 wt%, 78 wt%, 80 wt%, 82 wt%, 84 wt%, 86 wt%, or 88 wt%. The charging time of the fast-charging battery from 10% SOC to 80% SOC is ≤8.9 min, for example, it can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, or 8.9 min. For min, the corresponding fast-charging battery satisfies: 3.6≤(N×σ) / d≤18.9, for example, it can be 3.6, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 or 18.9, but it is not limited to the listed values. Other unlisted values ​​within this range also apply.

[0045] In some embodiments, the fast-charging battery is prepared using the following method:

[0046] (1) Preparation of positive electrode sheet: mixing a positive electrode active material and additives, adding a solvent to obtain a positive electrode slurry; coating the positive electrode slurry on at least one surface of a positive electrode current collector, and drying, rolling and slitting to obtain a positive electrode sheet.

[0047] Specifically, the additives include at least one of a conductive agent, a dispersant or a binder.

[0048] Those skilled in the art can select the dosages of the positive electrode active material, conductive agent, binder, dispersant and solvent according to requirements. For example, the mass ratio of the positive electrode active material, the conductive agent, the dispersant and the binder is (93-98.2):(0.5-3.1):(0.1-1.8):(1.2-3.5).

[0049] Specifically, the positive electrode active material is a nickel-cobalt ternary material or lithium iron phosphate, wherein the general chemical formula of the nickel-cobalt ternary material can be expressed as: Li a Ni b Co c M1 d M2 e O f R g , wherein 0.75≤a≤1.2, 0<b<1, 0<c<1, 0<d<1, b+c+d=1, 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3; M1 can be Mn and / or Al, M2 is selected from at least one of B, Zr, Ti, Si, Mo, La, Ce, Te, Nb, Ta, Si, Al, W, Sr, V, Y, Mg, Co or Li, the content of M2 in the nickel-cobalt ternary material is 100-10000 ppm; R includes but is not limited to at least one of N, F, S or Cl.

[0050] Specifically, lithium iron phosphate is a positive electrode active material with olivine-type crystal structure, which has the advantages of low cost and high safety, and its general chemical formula can be expressed as: LiFe 1-x M x PO y Q z , wherein x≤0.1, 3.85≤y≤4, 0≤z≤0.05; M is a doping element, including but not limited to at least one of Mn, Ni, Co, Cr, Cu, Bi or Sb, and the content of M in lithium iron phosphate is 500-5000 ppm.

[0051] For a positive electrode sheet using a nickel-cobalt ternary material as the positive electrode active material, the areal density after rolling is 200~280 g / m 2 , and the compacted density is 3.2~3.6 g / cm 3 ; for a positive electrode sheet using lithium iron phosphate as the positive electrode active material, the areal density after rolling is 350~600 g / m2 The compacted density is 2.3~2.8 g / cm³. 3 .

[0052] In the above positive electrode, the conductive agent is selected from at least one of superconducting carbon (SP), acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0053] In the above-mentioned positive electrode sheet, the binder is selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorinated acrylate resin.

[0054] In the aforementioned positive electrode sheet, the dispersant is selected from at least one of acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, hydrogenated nitrile butadiene rubber (HNBR), polyvinylpyrrolidone (PVP), or polyethylene glycol (PEG). When the positive electrode active material is selected from lithium iron phosphate and / or lithium manganese iron phosphate, a dispersant is used.

[0055] Specifically, the positive electrode current collector can be a composite current collector or a metal foil. For example, carbon-coated aluminum foil can be used as the current collector, with the aluminum foil thickness being 12 μm and the carbon coating layer thickness being 2 μm.

[0056] Specifically, the composite current collector includes a middle polymer layer and metal layers disposed on both sides of the polymer layer; wherein, the polymer layer includes polymer materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, its derivatives, its crosslinks or copolymers; the metal layer includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy.

[0057] (2) Preparation of negative electrode sheet: Mix negative electrode active material, conductive agent, dispersant and other raw materials, add solvent to obtain negative electrode slurry; coat the negative electrode slurry on at least one side of the negative electrode current collector, dry, roll and cut to obtain negative electrode sheet.

[0058] Specifically, the mass ratio of the negative electrode active material, conductive agent, and dispersant adopts a conventional ratio in the art. For example, the mass ratio of the negative electrode active material, conductive agent, and dispersant is (95.5-98.95):(0.5-2):(0.05-0.3).

[0059] In the aforementioned negative electrode sheet, the negative electrode active material is selected from graphite, and is divided into natural graphite and artificial graphite. The raw materials for preparing the artificial graphite include at least one of petroleum coke, needle coke, or coal tar pitch.

[0060] In the aforementioned negative electrode sheet, the negative electrode active material further contains a binder, which is selected from at least one of asphalt, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resin, polyvinyl alcohol (PVA), sodium alginate (SA), or sodium carboxymethyl cellulose (CMC); the waterborne acrylic resin may be at least one of polyacrylic acid (PAA), polymethacrylic acid (PMAA), sodium polyacrylate (PAAS), or polyacrylamide (PAM).

[0061] In the aforementioned negative electrode sheet, the conductive agent is selected from at least one of superconducting carbon (SP), conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0062] In the above-mentioned negative electrode sheet, the dispersant is selected from at least one of acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, hydrogenated nitrile butadiene rubber (HNBR), polyvinylpyrrolidone (PVP) or polyethylene glycol (PEG).

[0063] In the aforementioned negative electrode sheet, the negative electrode current collector is selected from metal foil or composite current collector.

[0064] Specifically, the metal foil can be copper or a copper alloy.

[0065] Specifically, the composite current collector includes a middle polymer layer and metal layers disposed on both sides of the polymer layer; wherein, the polymer layer includes polymer materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, its derivatives, its crosslinks or copolymers; the metal layer includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy.

[0066] (3) Electrolyte preparation: Mix organic solvents, then dissolve the dried lithium salt in the mixed solvent, and then add additives to obtain the electrolyte.

[0067] In the above electrolyte, the lithium salt concentration is 0.5~2.5 mol / L, and the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiDFOB), lithium tetrafluoroborate (LiBF4), or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0068] The solvent in the above electrolyte includes at least one of cyclic carbonates, chain carbonates, carboxylic acid esters, or ethers.

[0069] In the electrolyte, the additives account for 0.5 wt% to 10 wt% of the total mass, and the additives include at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), or ethylene disulfide (BiDTD).

[0070] (4) Separator: It is placed between the positive electrode and the negative electrode to separate the positive electrode and the negative electrode and prevent the positive electrode and the negative electrode from short-circuiting.

[0071] The material of the diaphragm is selected from at least one of glass fiber, nonwoven fabric, polyethylene (PE), polypropylene (PP) or polyvinylidene fluoride.

[0072] Specifically, a coating may also be provided on the surface of the diaphragm. The coating may be an inorganic coating and / or an organic coating. The inorganic coating material includes at least one of alumina, silicon oxide, titanium oxide, magnesium oxide, zirconium oxide or boehmite. The organic coating includes at least one of aramid coating or polyvinylidene fluoride (PVDF) coating.

[0073] (5) The above positive electrode sheet, separator and negative electrode sheet are wound in sequence to obtain a bare cell; the bare cell is placed in a cylindrical shell, dried, injected with electrolyte, and then packaged, left to stand and formed to obtain a fast-charging battery.

[0074] One embodiment of the present invention also provides an electrical device, the electrical device comprising the fast-charging battery described in any of the above embodiments.

[0075] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0076] Examples 1-15

[0077] This set of embodiments provides a fast-charging battery, including a positive electrode, a separator, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode active material containing graphite. The negative electrode active material includes secondary particles formed by the agglomeration of primary particles and single particles dispersed between the primary and secondary particles (micrograph of the negative electrode active material obtained in Example 1 is shown in...). Figure 1 The average number of primary particles N in the secondary particles, the average particle size d μm of the primary particles, the ionic conductivity σ mS / cm of the electrolyte at 25℃, and the relationship between the above three parameters are detailed in Table 1 below.

[0078] Table 1

[0079]

[0080] In addition, in each embodiment, the OI value of the negative electrode active material, the long axis A μm, the short axis C μm and the sphericity ψ of the primary particles, the volume ratio φ1 of the single particles in the negative electrode active material and the volume ratio φ2 of the secondary particles in the negative electrode active material are detailed in Table 2 below.

[0081] Table 2

[0082]

[0083] Specifically, the fast-charging batteries provided in each embodiment are manufactured using the following method:

[0084] (1) Preparation of positive electrode: The nickel-cobalt-manganese ternary material LiNi 0.8 Co 0.1 Mn 0.1O2, conductive agent SWCNT (single-walled carbon nanotubes), dispersant CMC, and binder SBR are mixed evenly in a mass ratio of 95:2:1:2. N-methylpyrrolidone is then added to obtain a positive electrode slurry with a solid content of 75 wt%. This slurry is then coated onto both sides of an aluminum foil, dried, rolled, and slit to obtain a compacted density of 3.5 g / cm³. 3 The positive electrode plate.

[0085] (2) Preparation of negative electrode sheet: First, petroleum coke is pre-calcined, crushed, graded and cut to obtain artificial graphite. Then, it is mixed with asphalt binder, granulated and sheared to obtain negative electrode active material (process parameters for each step are detailed in Table 3). The obtained negative electrode active material, conductive agent SWCNT and dispersant CMC are mixed evenly at a mass ratio of 98.8:1:0.2. Deionized water is added to obtain a negative electrode slurry with a solid content of 55wt%. Then, the negative electrode slurry is coated on both sides of copper foil, dried, rolled and cut to obtain a compacted density of 1.6 g / cm³. 3 The negative electrode.

[0086] Table 3

[0087]

[0088] In the table above, the pre-calcination temperature and the graded particle size have a combined effect on the average particle size d μm of the primary particles in the graphite anode. As the pre-calcination temperature or the graded particle size increases, the average particle size d μm of the resulting primary particles in the graphite anode also increases. The grinding intensity and the asphalt ratio have a combined effect on the average number N of primary particles contained in the secondary particles of the graphite anode. As the grinding intensity decreases or the asphalt ratio increases, the average number N of primary particles contained in the secondary particles of the resulting graphite anode also increases.

[0089] (3) Electrolyte preparation: DMC, EMC and DEC are mixed evenly according to the volume ratio in Table 4. Dry LiFSI and LiPF6 (mass ratio is detailed in Table 4) are added to prepare an electrolyte with a lithium salt concentration of 1 mol / L. Then FEC is added and its content in the electrolyte is controlled to be 5 wt%.

[0090] Table 4

[0091]

[0092] In the table above, the combined effects of DMC and LiFSI content on the ionic conductivity σmS / cm of the electrolyte at 25℃ are shown. As the DMC or LiFSI content increases, the ionic conductivity σmS / cm of the resulting electrolyte at 25℃ also increases.

[0093] (4) PP film is selected as the separator.

[0094] (5) The above positive electrode sheet, separator and negative electrode sheet are wound in sequence to obtain a bare cell; the bare cell is placed in a cylindrical shell, dried, injected with electrolyte, and then packaged, left to stand and formed to obtain a fast-charging battery.

[0095] Comparative Examples 1-4

[0096] This comparative example provides a fast-charging battery, including a positive electrode, a separator, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode active material containing graphite. The negative electrode active material includes secondary particles formed by the agglomeration of primary particles and single particles discrete in the primary and secondary particles. The average number of primary particles N in the secondary particles, the average particle size d μm of the primary particles, the ionic conductivity σ mS / cm of the electrolyte at 25°C, and the relationship between the above three parameters are detailed in Table 5 below.

[0097] Table 5

[0098]

[0099] In addition, the OI value of the negative electrode active material, the major axis A μm, the minor axis C μm and the sphericity ψ of the primary particles, the volume ratio φ1 of the single particle in the negative electrode active material and the volume ratio φ2 of the secondary particles in the negative electrode active material are detailed in Table 6 below.

[0100] Table 6

[0101]

[0102] Specifically, the fast-charging batteries provided in each comparative example are manufactured using the following method:

[0103] (1) Preparation of positive electrode: The nickel-cobalt-manganese ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent SWCNT (single-walled carbon nanotubes), dispersant CMC, and binder SBR are mixed evenly in a mass ratio of 95:2:1:2. N-methylpyrrolidone is then added to obtain a positive electrode slurry with a solid content of 75 wt%. This slurry is then coated onto both sides of an aluminum foil, dried, rolled, and slit to obtain a compacted density of 3.5 g / cm³. 3 The positive electrode plate.

[0104] (2) Preparation of negative electrode sheet: First, petroleum coke is pre-calcined, crushed, graded and cut to obtain artificial graphite. Then, it is mixed with asphalt binder, granulated and sheared to obtain negative electrode active material (process parameters for each step are detailed in Table 7). The obtained negative electrode active material, conductive agent SWCNT and dispersant CMC are mixed evenly at a mass ratio of 98.8:1:0.2. Deionized water is added to obtain a negative electrode slurry with a solid content of 55wt%. Then, the negative electrode slurry is coated on both sides of copper foil, dried, rolled and cut to obtain a compacted density of 1.6 g / cm³. 3 The negative electrode.

[0105] Table 7

[0106]

[0107] (3) Electrolyte preparation: DMC, EMC and DEC are mixed evenly according to the volume ratio in Table 8. Dry LiFSI and LiPF6 (mass ratio is detailed in Table 8) are added to prepare an electrolyte with a lithium salt concentration of 1 mol / L. Then FEC is added and its content in the electrolyte is controlled to be 5 wt%.

[0108] Table 8

[0109]

[0110] (4) PP film is selected as the separator.

[0111] (5) The above positive electrode sheet, separator and negative electrode sheet are wound in sequence to obtain a bare cell; the bare cell is placed in a cylindrical shell, dried, injected with electrolyte, and then packaged, left to stand and formed to obtain a fast-charging battery.

[0112] In Tables 1-2 and 5-6, the parameters were tested using the following methods:

[0113] (a) The average number of primary particles N contained in secondary particles: After discharging the battery at 0.33C to the lower limit cutoff voltage of 2.5V, the cell was disassembled, the negative electrode sheet was removed and the negative electrode active material was peeled off, the obtained sample was cold-mounted and polished, the secondary particles were cut open, the cross-sectional morphology was photographed by scanning electron microscope, the internal primary particles were clearly identified, a sufficient number of secondary particles were randomly selected, the number of primary particles inside a single particle was counted, the counting results were summarized, and the average number N was calculated.

[0114] (b) Average particle size d μm of primary particles: Based on the above test method, select a sufficient number of complete primary particles, divide the cross-sectional area occupied by all particles by the total number of particles to obtain the cross-sectional area occupied by a single primary particle, and calculate the diameter of the equivalent area circle as the average particle size d μm of the primary particles.

[0115] (c) Ionic conductivity of electrolyte at 25℃ σ mS / cm: Using an electrochemical workstation, the temperature is controlled at 25℃. The bulk resistance R of the electrolyte is tested by AC impedance method, and the ionic conductivity σ = L / (R×A) is calculated; where L is the distance between the two electrodes (i.e. the thickness of the electrolyte), and A is the effective contact area between the electrode and the electrolyte.

[0116] (d) OI value of negative electrode active material: After discharging the battery at 0.33C to the lower limit cutoff voltage of 2.5V, the cell was disassembled, the negative electrode sheet was removed and the graphite material was peeled off. The XRD pattern of graphite at 10-90° was tested using an X-ray diffractometer. The pattern was fitted and the peak area ratio of the (004) crystal plane and the (110) crystal plane was calculated, i.e., OI value = I(004) / I(110), where I is the diffraction peak area.

[0117] (e) Major axis A μm, minor axis C μm, and sphericity ψ of primary particles: After discharging the battery at 0.33C to the lower cutoff voltage of 2.5V, the cell was disassembled, the negative electrode sheet was removed, and the negative electrode active material was peeled off. The resulting sample was cold-mounted, polished, and the secondary particles were cut open. The cross-sectional morphology was photographed using a scanning electron microscope. A sufficient number of primary particles were selected, and the major and minor axis dimensions were measured and the average values ​​were calculated. Then, the sphericity ψ = C / ((A μm) was calculated based on the major axis A μm and the minor axis C μm. 2 +AC) / 2) 1 / 2 .

[0118] (f) Volume percentage of single particles and secondary particles in negative electrode active material φ1% and φ2%: After discharging the battery at 0.33C to the lower limit cutoff voltage of 2.5V, the cell was disassembled, the negative electrode sheet was removed and the negative electrode active material was peeled off. The obtained sample was cold-mounted and polished. The morphology image was taken by electron microscope to distinguish the two types of particles. The area percentage was calculated by using image software and the volume percentage was equivalently converted.

[0119] Performance testing

[0120] (1) Fast charging performance: A three-electrode battery was prepared and charged using Xinwei equipment (copper wire as auxiliary electrode). First, it was charged at 1C to 5% SOC, then at 3C to 10% SOC, and then charged at 8C, 7C, 6.5C, 5.5C, 5C, 4.6C, 4.2C, 3.8C, 3.4C, 3C, 2.6C, 2.2C, 1.8C, 1.6C, 1.4C, 1.2C, 1C, 0.8C, 0.6C, 0.4C, 0.2C, 0.1C, and 0.05C. The charging cutoff condition was that the three-electrode auxiliary voltage dropped to 0mV. Based on the charging capacity and the corresponding step time, the charging time of the battery from 10% SOC to 80% SOC was calculated.

[0121] (2) High temperature storage performance: After cycling the battery at 0.33C for 2 cycles, adjust the load to 50% SOC, test 1C DCR (discharge 18s, charge 10s), and then charge at 0.33C to the upper limit voltage of 4.25 V; place it in a 70℃ constant temperature chamber, and after placing it at 0D, 10D, 50D and 90D respectively, measure and calculate the capacity retention rate of the battery after different placement times.

[0122] Table 9

[0123]

[0124] As shown in the table above, for the fast-charging batteries prepared in Examples 1 to 15, since they meet the limiting condition of 3.1≤(N×σ) / d≤21.7, their charging time from 10% SOC to 80% SOC is ≤15 min, and their capacity retention rate at different placement times at 70℃ remains at a high level. It can be seen that their fast-charging performance and high-temperature storage performance have been synergistically optimized.

[0125] Compared to Examples 1-15, the fast-charging battery prepared in Comparative Example 1, although the key parameters N, d, and σ are all within the protection range, has (N×σ) / d < 3.1, which ultimately leads to an extension of the charging time from 10% SOC to 80% SOC to 18 minutes, i.e., a significant reduction in fast-charging performance. Conversely, the fast-charging battery prepared in Comparative Example 2, although the key parameters N, d, and σ are all within the protection range, has (N×σ) / d > 21.7, which ultimately leads to a significant reduction in its capacity retention rate at different storage times at 70°C, i.e., a significant reduction in high-temperature storage performance.

[0126] Compared to Examples 1-15, the fast-charging battery prepared in Comparative Example 3 not only had the key parameters N, d, and σ all outside the protection range, but also had (N×σ) / d < 3.1, which ultimately led to an extension of the charging time from 10% SOC to 80% SOC to 20 minutes, meaning that the fast-charging performance was significantly reduced. Conversely, the fast-charging battery prepared in Comparative Example 4 not only had the key parameters N, d, and σ all outside the protection range, but also had (N×σ) / d > 21.7, which ultimately led to a significant reduction in its capacity retention rate at different storage times at 70°C, meaning that its high-temperature storage performance was significantly reduced.

[0127] As can be seen, the fast-charging battery provided by the present invention achieves dynamic matching between the microstructure of the negative electrode and the conductivity of the electrolyte by synergistically adjusting key parameters such as the average number of primary particles in the secondary particles of the graphite negative electrode, the average particle size of the primary particles, and the ionic conductivity of the electrolyte. This effectively opens up the lithium-ion transport channel and shortens the diffusion path, thus well balancing the dynamics and high-temperature storage performance of the fast-charging battery.

[0128] As can be seen, the fast-charging battery provided by the present invention achieves dynamic matching between the microstructure of the negative electrode and the conductivity of the electrolyte by synergistically adjusting key parameters such as the average number of primary particles in the secondary particles of the graphite negative electrode, the average particle size of the primary particles, and the ionic conductivity of the electrolyte. This effectively opens up the lithium-ion transport channel and shortens the diffusion path, thus well balancing the dynamics and high-temperature storage performance of the fast-charging battery.

[0129] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A fast-charging battery, comprising a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode active material, the negative electrode active material containing graphite, characterized in that, The charging time for the fast-charging battery from 10% SOC to 80% SOC is ≤15 min; The negative electrode active material includes secondary particles formed by the agglomeration of primary particles. The average number of primary particles in the secondary particles is set to N, the average particle size of the primary particles is d μm, and the ionic conductivity of the electrolyte at 25℃ is σ mS / cm. Then, the following condition is satisfied: 3.1≤(N×σ) / d≤21.

7.

2. The fast-charging battery according to claim 1, characterized in that, The OI value of the negative electrode active material is 2~3.

84.

3. The fast-charging battery according to claim 2, characterized in that, The OI value of the negative electrode active material is 2.5~3.

5.

4. The fast-charging battery according to claim 1, characterized in that, The average number N of primary particles contained in the secondary particles is 3 to 15.

5. The fast-charging battery according to claim 4, characterized in that, The average number N of primary particles contained in the secondary particles is 4 to 8.

6. The fast-charging battery according to claim 1, characterized in that, The average particle size d μm of the primary particles is 3~9.8 μm.

7. The fast-charging battery according to claim 6, characterized in that, The average particle size d μm of the primary particles is 3.2~4.7 μm.

8. The fast-charging battery according to claim 1, characterized in that, The electrolyte has an ionic conductivity σmS / cm of 6.1~12.8 mS / cm at 25℃.

9. The fast-charging battery according to claim 8, characterized in that, The electrolyte has an ionic conductivity σmS / cm of 8.3~9.7 mS / cm at 25℃.

10. The fast-charging battery according to claim 1, characterized in that, The charging time for the battery from 10% SOC to 80% SOC is ≤12 min.

11. The fast-charging battery according to claim 1, characterized in that, The sphericity of the primary particles is ≥0.

5.

12. The fast-charging battery according to claim 11, characterized in that, The major axis of the primary particles is 6~12 μm.

13. The fast-charging battery according to claim 11 or 12, characterized in that, The minor axis of the primary particles is 2.8~7.4 μm.

14. The fast-charging battery according to claim 1, characterized in that, The negative electrode active material also includes single particles discrete between primary and secondary particles.

15. The fast-charging battery according to claim 14, characterized in that, The volume percentage of the single particles in the negative electrode active material is 5% to 20%.

16. The fast-charging battery according to claim 14, characterized in that, The secondary particles account for 70% to 90% of the volume of the negative electrode active material.

17. The fast-charging battery according to claim 15 or 16, characterized in that, The total volume ratio of single particles and secondary particles in the negative electrode active material is 75% to 95%.

18. The fast-charging battery according to claim 1, characterized in that, The electrolyte contains a lithium salt, which includes at least one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalate borate, lithium tetrafluoroborate, or lithium bis(trifluoromethanesulfonyl)imide.

19. The fast-charging battery according to claim 18, characterized in that, The lithium salt is selected from lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.

20. The fast-charging battery according to claim 19, characterized in that, The mass ratio of lithium difluorosulfonylimide to lithium hexafluorophosphate is (0.1~0.8):(0.2~0.9).

21. The fast-charging battery according to claim 1, characterized in that, The electrolyte contains a solvent, which includes at least one of cyclic carbonates, chain carbonates, carboxylic acid esters, or ethers.

22. The fast-charging battery according to claim 21, characterized in that, The solvent is selected from chain carbonates, which include at least one of methyl ethyl carbonate, dimethyl carbonate, or diethyl carbonate.

23. The fast-charging battery according to claim 22, characterized in that, The chain carbonate has ≤5 carbon atoms.

24. The fast-charging battery according to claim 1, characterized in that, The electrolyte contains additives, including at least one of fluoroethylene carbonate, vinylene carbonate, or ethylene bisulfate.

25. The fast-charging battery according to claim 24, characterized in that, The additive accounts for 0.5 wt% to 10 wt% of the mass of the electrolyte.

26. The fast-charging battery according to claim 1, characterized in that, The fast-charging battery also includes a positive electrode sheet, which includes a positive electrode material containing lithium iron phosphate. The charging time of the fast-charging battery from 10% SOC to 80% SOC is ≤12 min.

27. The fast-charging battery according to claim 26, characterized in that, The fast-charging battery satisfies: 3.2≤(N×σ) / d≤17.

8.

28. The fast-charging battery according to claim 1, characterized in that, The fast-charging battery also includes a positive electrode sheet, which includes a positive electrode material containing a ternary material. The nickel content in the ternary material is 60 wt% to 88 wt%, and the charging time of the fast-charging battery from 10% SOC to 80% SOC is ≤8.9 min.

29. The fast-charging battery according to claim 28, characterized in that, The fast-charging battery satisfies: 3.6≤(N×σ) / d≤18.

9.

30. An electrical device, characterized in that, The electrical device includes a fast-charging battery as described in any one of claims 1 to 29.